Sequential Detection of Physical Network Coding in the Presence of Phase Asynchrony - Marchand, Philippe (University of Ottawa (Canada), 2010)
Physical-Layer Network Coding has the potential to greatly increase the throughput of wireless networks. This novel method of operating networks is based on the coherent demodulation of signals containing two waveforms transmitted synchronously. In this thesis, we explore the problems imposed by the physical constraints, in particular the carrier phase offset of the two signals making up the physical network code (PNC). For QPSK transmissions, coherent demodulation of the resulting symbols will be penalized by a decreased minimum distance resulting from carrier phase misalignment. Based on the observation that binary signalling is not affected by this asynchrony, we propose a modulation framework which enables the coherent demodulation of PNC symbols with arbitrary phase offsets. The framework is based on bit-offset modulation by the sources and Maximum-Likelihood Sequence Detection by the receiver. The spread in receiver performance for a range of phase offset PNC signals is less than 2dB at moderate SNR for transmissions at a rate of 2 bits/symbol. These results confirm that the proposed solution is able to solve the problem of phase asynchrony for PNC QPSK and higher order modulations.
Keywords: Engineering, Electronics and Electrical.